2016
DOI: 10.1155/2016/7541468
|View full text |Cite
|
Sign up to set email alerts
|

Impact Response of Quasi-Isotropic Asymmetric Carbon Fabric/Epoxy Laminate Infused with MWCNTs

Abstract: Effect of embedding multiwalled carbon nanotubes (MWCNTs) on low velocity impact response of quasi-isotropic asymmetric laminate of plain woven carbon fabric/epoxy was investigated. Laminates were embedded with 0 wt.%, 2 wt.%, and 5 wt.% MWCNTs to improve impact resistance. Impact in laminates was conducted according to ASTM D7136 standard at an impact energy of 94.14 J corresponding to the impact velocity of 6 m/sec. Energy-time response, force-time response, and pyramidal damage area of laminates doped with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Singh et al. [37] have reported that in case of asymmetric laminate with quasi-isotropic lay-up for plain CFRP, absorbed energy and damage area are correspondingly increased by 13.53 % and reduced on doping of 2 wt. % of MWCNTs, while doping of 5 wt.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al. [37] have reported that in case of asymmetric laminate with quasi-isotropic lay-up for plain CFRP, absorbed energy and damage area are correspondingly increased by 13.53 % and reduced on doping of 2 wt. % of MWCNTs, while doping of 5 wt.…”
Section: Introductionmentioning
confidence: 99%
“…al. [10] conducted the LVI experimental work on asymmetric CFRP laminate doped with MWCNTs and observed that 2wt.% was the optimum doping weight percentage and beyond which properties were degraded. CFRP laminate with 2wt.% MWCNTs showed 13.53% enhancement in energy absorption and reduction in pyramidal damage when compared with neat asymmetric CFRP laminate.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties like modulus ( E ), hardness ( H ) and fracture toughness ( K IC ) of the polymer materials can be improved by addition of small volumes of high quality and high strength nano-particles like CNT, 2426 graphene, GO, etc. The present work is an attempt to harness the mechanical properties of GO as reinforcement in bisphenol-A (BPA)-based polymer matrix nano-composites.…”
Section: Introductionmentioning
confidence: 99%